Differential susceptibility according to gender in the association between air pollution and mortality from respiratory diseases - Marcio Sacramento de Oliveira; Antônio Ponce de Leon; Inês Echenique Mattos; Sérgio Koifman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study analyzed the association between air pollution and deaths from respiratory diseases, considering differential susceptibility according to gender. The authors used daily deaths from respiratory diseases (ICD-10, J00-J99), PM10, SO2, and O3 levels, and meteorological indicators in Volta Redonda, Rio de Janeiro State, Brazil, from January 2002 to December 2006. The association was estimated by Poisson regression using generalized additive models, where the increase in risk of deaths from PM10 to lag 1 was 10.01% (95%CI: 1.81-18.88%) in the total female population and 10.04% (95%CI: 0.90-20.02%) in elderly women. The increase in risk of deaths from PM10 to lag 9 was 8.25% in the total male population (95%CI: 0.86-16.18%) and 10.80% (95%CI: 2.18-20.15%) in elderly men. For exposure to SO2 and O3, the risk was significant in the total male population and the elderly, respectively. The results emphasize the need for further studies, focusing on modification of the effects of air pollution on health.